2009
DOI: 10.1093/jpepsy/jsp007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effects on Depressive Symptoms and Self-Worth in Overweight Children: A Randomized Controlled Trial

Abstract: This study shows dose-response benefits of exercise on depressive symptoms and self-worth in children. However, Blacks did not show increased GSW in response to the intervention. Results provide some support for mediation of the effect of exercise on depressive symptoms via self-worth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 37 publications
2
63
1
6
Order By: Relevance
“…Encouragingly, this outcome is what was observed in the majority of these studies. In 1 study, 59 the effect of an aerobic exercise intervention on depressive symptoms among overweight children was partially mediated by changes in perceived appearance and global self-worth. This study suggests that perceptions of the self are indeed related to ill-being in youth.…”
Section: Psychosocial Mechanismsmentioning
confidence: 96%
See 1 more Smart Citation
“…Encouragingly, this outcome is what was observed in the majority of these studies. In 1 study, 59 the effect of an aerobic exercise intervention on depressive symptoms among overweight children was partially mediated by changes in perceived appearance and global self-worth. This study suggests that perceptions of the self are indeed related to ill-being in youth.…”
Section: Psychosocial Mechanismsmentioning
confidence: 96%
“…24 -26 In the studies included in the current review, relatedness was often operationalized as "social acceptance" (ie, the belief that one is valued and accepted by others). Social acceptance was measured in 3 studies, 58,59,68 and each of these studies also examined the effects of interventions on self-esteem. Interestingly, although significant intervention effects were reported for social acceptance in only 1 study, 58 improvements in self-esteem were found in all 3 studies.…”
Section: Psychosocial Mechanismsmentioning
confidence: 99%
“…The Society of Behavioral Medicine supports physical activity promotion among all age groups but focuses this position statement specifically on elementary schoolchildren, given the preponderance of the evidence in this group and differing physical activity recommendations across the lifespan. activity improves cardiorespiratory fitness and mood and results in brain changes [4]. Regular physical activity improves executive function, and acute bouts improve attention and time on task [3,18].…”
Section: Researchmentioning
confidence: 99%
“…Regular physical activity improves cognitive function, induces brain changes, and improves mood in children, in addition to improving their aerobic fitness [3][4][5][6][7][8]. Greater aerobic fitness and physical activity are associated cross sectionally with increased grade point averages and standardized test scores [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Las conclusiones de estos estudios ponen de relieve los vínculos existentes entre factores como la fuerza o la capacidad cardiorrespiratoria con medidas generales de autoconcepto y otras específicas como el autoconcepto físico, intelectual o social (Guillén y Ramírez, 2011;Petty, Davis, Tkacz, Young-Hyman y Waller, 2009;Sherrill, Holguin y Caywood, 1989;Strong et al, 2005;Vedul-Kjelsäs, Sigmundsson, Stensdotter y Haga, 2012;Velez et al, 2010). En la presente investigación, aunque la velocidad, la flexión profunda de tronco y el salto horizontal han correlacionado significativamente con las diferentes dimensiones del autoconcepto estudiado, el consumo máximo de oxígeno es la medida que más relevancia ha tenido.…”
Section: Discussionunclassified